Glycemic control and awareness among diabetic patients of nutrition recommendations in diabetes - Karolina Ruszkiewicz; Paweł Jagielski; Iwona Traczyk (National Institute of Public Health - National Institute of Hygiene, 2020)
Background. The incidence of diabetes has been rising rapidly, especially in urbanized countries. It is estimated that by 2035 the number of diabetics will have increased to almost 600 million around the world. There is a substantial amount of evidence which points to proper education as one of the most effective ways of delaying the diabetes-related development of complications. Objective. The aim of the study was to investigate the frequency of monitoring blood sugar by diabetic patients and their awareness of nutrition recommendations in diabetes. Materials and methods. The study included 303 patients with type 1 and 2 diabetes. The research tool was a questionnaire based on the KomPAN questionnaire that consisted of a nutrition knowledge test and several questions concerning glycaemic control. The statistical analysis was carried out using the PS IMAGO PRO 5 (IBM SPSS Statistics 25) software. Results. Most of the patients demonstrated a medium level of knowledge - 62% of them provided >50% of the correct answers. Only 8% of the respondents scored >80% of the correct answers. Better test results were achieved by patients with type 1 diabetes. The highest percentage of correct answers was observed in the questions regarding the need to limit sweets or introduce fibre-rich whole-grain products (>90%), the smallest percentage in the questions related to the assessment of carbohydrates and the glycaemic index of selected products (<30%). The majority of the patients checked their blood sugar levels every day, but 6% of them gave up glucose measurements at home. About half of the respondents did not take the HbA1c test - the majority of them were patients with type 2 diabetes. Conclusions. The level of knowledge of the examined patients was unsatisfactory and varied with the type of diabetes. Further education of patients about nutrition and glycaemic control is recommended.